Peningkatan Keterampilan PHBS pada Suku Anak Dalam (SAD) melalui Metode Demonstrasi dan Pendampingan Individu - Aisyah Putri Ramadani; Zaskia Nabila Mecca; Sukma Ayu Ningsi; Sinta Agrecilia Br Sembiring; Asparian Asparian (Universitas Baiturrahim, 2026)
Suku Anak Dalam (SAD) is an indigenous community living in the forests of Jambi and South Sumatra, also known as Orang Rimba, who have a unique culture and traditions that are deeply tied to nature. Their life is nomadic or what they usually call melangun. With a nomadic lifestyle, it is difficult for them to obtain sources of information or sources of knowledge, especially in the health sector. This community service aims to provide a comprehensive overview of the effectiveness of health education interventions in improving Clean and Healthy Living Behavior (PHBS) in children in the Suku Anak Dalam (SAD) community in Lantak Seribu Village, Renah Pamenang District, Merangin Regency. The population of the community service is all children aged 4-15 years in the area. This community service discusses PHBS with a focus on three main topics: Washing Hands with Soap (CTPS), Happy Nail Clipping, and dental and oral hygiene practices. The approach used through visual methods, demonstrations, direct training, educational games, and pretest-posttest evaluations is able to meet the needs in the field and is in line with the initial problems identified. The results of community service show that the experiential education method is very appropriate for SAD children, who tend to learn through visual and kinesthetic means, and this activity has a positive impact on the understanding and practice of personal hygiene, and encourages children's awareness to adopt healthy behaviors independently.